Major league - Ward, D. S.; Berenger, Tom, 1950-; Sheen, Charlie; Bernsen, Corbin, 1954- (Hollywood, Calif. : Paramount Home Video, 2002)
When she inherits the Cleveland Indians, a woman hires what she thinks will be a losing line up so she can move the team to Miami.
Tom Berenger, Charlie Sheen, Corbin Bernsen, Margaret Whitton, James Gammon.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
In English or French with optional English subtitles.
Closed-captioned.
Keywords: Baseball -- Drama; Video recordings for hard of hearing people; Feature films; Comedy films